Poles in Illinois - Radzilowski, John, 1965-; Gunkel, Ann Hetzel, 1963- (Southern Illinois University Press, 2020)
"This short, clear, and comprehensive history of Poles in the state of Illinois from 1818 to the present shows a rich story of diversity and the changing nature of Polish ethnicity in the state over the past 200 years"--